2007
DOI: 10.1080/14659890701262262
|View full text |Cite
|
Sign up to set email alerts
|

Views of alcohol control policies in the 2000 National Alcohol Survey: What news for alcohol policy development in the US and its States?

Abstract: This article examines public opinion in US alcohol policies during the 1990s and their correlates in 2000, using five national telephone surveys. Trend analyses of public opinion on 11 common alcohol policies is presented and factor-based policy scales, based on 14 items in 2000, are used to examine demographic correlates of support for various policy areas, using bivariate, linear (OLS) and logistic regression analyses. With the exception of the alcohol warning label policy, national support for alcohol polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 33 publications
3
61
1
Order By: Relevance
“…Consistent with previous studies, we found that support for restrictive measures decreased with increased consumption and increased with age, and that it was stronger among women than among men (e.g., Giesbrecht et al, 2005;Greenfield et al, 2007b;van der Sar et al, 2012). The finding indicating that support increased with level of education, is consistent with results from a recent study in Sweden (Holmberg & Weibull, 2013), but deviates from other studies (e.g., van der Sar et al, 2012;Wilkinson et al, 2009).…”
Section: Demographics and Own Drinkingsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies, we found that support for restrictive measures decreased with increased consumption and increased with age, and that it was stronger among women than among men (e.g., Giesbrecht et al, 2005;Greenfield et al, 2007b;van der Sar et al, 2012). The finding indicating that support increased with level of education, is consistent with results from a recent study in Sweden (Holmberg & Weibull, 2013), but deviates from other studies (e.g., van der Sar et al, 2012;Wilkinson et al, 2009).…”
Section: Demographics and Own Drinkingsupporting
confidence: 91%
“…Accordingly, previous studies have repeatedly shown that support for such restrictions decreases with increasing consumption (e.g., Giesbrecht, Ialomiteanu, & Anglin, 2005;Greenfield et al, 2007b;van der Sar et al, 2012).…”
Section: Possible Predictorsmentioning
confidence: 96%
“…Support for government controls might vary by race/ ethnicity and other demographics; Latinos, females, and alcohol abstainers have tended to favor limiting the number of liquor licenses in their communities (Jones-Webb et al, 1993), whereas older adults favored policies that restrict alcohol use in public places (Latimer et al, 2001). Perhaps not surprisingly, high-risk drinkers, who are the primary targets of price and availability controls, have been generally less likely to disagree with privatization compared with other drinkers (Anglin et al, 2001(Anglin et al, , 2003Greenfield et al, 2007b).…”
mentioning
confidence: 99%
“…Women and older individuals have relatively more positive attitudes to intrusive policy measures (Doucet, Velicer, & Laforge, 2007;Giesbrecht, Lalomiteanu, Anglin, & Adlaf, 2007;Greenfield, Ye, & Giesbrecht, 2007;Holmila, Mustonen, Österberg, & Raitasalo, 2009;Matheson et al, 2013;Saglie & Nordlund, 1993;Storvoll, Moan, & Rise, 2014;Wilkinson, Room, & Livingston, 2009). …”
mentioning
confidence: 99%